2021
DOI: 10.1002/ijc.33557
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of probiotics on the efficacy of anti‐PD‐1 monotherapy in patients with nonsmall cell lung cancer: A multicenter retrospective survival analysis study with inverse probability of treatment weighting

Abstract: The gastrointestinal microbiota was reported as an important factor for the response to cancer immunotherapy. Probiotics associated with gastrointestinal dysbiosis and bacterial richness may affect the efficacy of cancer immunotherapy drugs. However, the clinical impact of probiotics on the efficacy of cancer immunotherapy in patients with nonsmall cell lung cancer (NSCLC) is poorly understood. The outcomes of 294 patients with advanced or recurrent NSCLC who received antiprogrammed cell death-1 (PD-1) therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Recent preliminary results of clinical studies have shown the ability of live biotherapeutic bacterium to induce compositional shifts in the gut microbiome and to provide the positive impact on the clinical benefit to ICB. 4 , 20 , 22 , 42 However, the impact of CBM588 on gut microbiota in patients with thoracic cancer had remained unknown. In the current study, we found patients who received CBM588 had a lesser abundance of potentially harmful oral-related bacterial genera, Atopobium and Streptococcus , 26 , 27 suggesting that CBM588 may have the potential to shift the gut dysbiosis to a favorable microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Recent preliminary results of clinical studies have shown the ability of live biotherapeutic bacterium to induce compositional shifts in the gut microbiome and to provide the positive impact on the clinical benefit to ICB. 4 , 20 , 22 , 42 However, the impact of CBM588 on gut microbiota in patients with thoracic cancer had remained unknown. In the current study, we found patients who received CBM588 had a lesser abundance of potentially harmful oral-related bacterial genera, Atopobium and Streptococcus , 26 , 27 suggesting that CBM588 may have the potential to shift the gut dysbiosis to a favorable microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter and retrospective study conducted by Takada K et al has demonstrated that probiotics are linked to beneficial clinical outcomes in patients with advanced or recurrent NSCLC treated with anti-PD-1 monotherapy [ 120 ]. However, another study has reported paradoxical results in melanoma patients who took probiotic supplements while receiving immunotherapy and had a worse survival outcome.…”
Section: Gut Microbiota and Response To Systemic Therapy Including Im...mentioning
confidence: 99%
“…Clinically, Toi et al discovered that Lactobacillus casei strain Shirota consumption showed a negative correlation with breast cancer incidence (OR = 0.65, p = 0.048) [ 299 ]. Takada et al demonstrated that supplementation with probiotics improved progression-free survival (HR = 1.73, p = 0.0229), disease control (OR = 0.51, p = 0.0004), and overall response (OR = 0.43, p < 0.0001) in NSCLC patients receiving anti-programmed cell death 1 protein (anti-PD-1) monotherapy [ 300 ]. Additionally, the use of probiotics decreased the incidence of metachronous gastric cancer after endoscopic resection (HR = 0.29, p = 0.034) [ 301 ].…”
Section: Emerging Approaches: Interventions In the Gut Microbiota In ...mentioning
confidence: 99%